CHIT1 at Diagnosis Reflects Long‐Term Multiple Sclerosis Disease Activity. Issue 4 (8th February 2020) - Oldoni, Emanuela; Smets, Ide; Mallants, Klara; Vandebergh, Marijne; Van Horebeek, Lies; Poesen, Koen; Dupont, Patrick; Dubois, Bénédicte; Goris, An
Abstract : Objective: Evidence for a role of microglia in the pathogenesis of multiple sclerosis (MS) is growing. We investigated association of microglial markers at time of diagnostic lumbar puncture (LP) with different aspects of disease activity (relapses, disability, magnetic resonance imaging parameters) up to 6 years later in a cohort of 143 patients. Methods: In cerebrospinal fluid (CSF), we measured 3 macrophage and microglia‐related proteins, chitotriosidase (CHIT1), chitinase‐3–like protein 1 (CHI3L1 or YKL‐40), and soluble triggering receptor expressed on myeloid cells 2 (sTREM2), as well as a marker of neuronal damage, neurofilament light chain (NfL), using enzyme‐linked immunosorbent assay and electrochemiluminescence. We investigated the same microglia‐related markers in publicly available RNA expression data from postmortem brain tissue. Results: CHIT1 levels at diagnostic LP correlated with 2 aspects of long‐term disease activity after correction for multiple testing. First, CHIT1 increased with reduced tissue integrity in lesions at a median 3 years later ( p = 9.6E‐04). Second, CHIT1 reflected disease severity at a median 5 years later ( p = 1.2E‐04). Together with known clinical covariates, CHIT1 levels explained 12% and 27% of variance in these 2 measures, respectively, and were able to distinguish slow and fast disability progression (area under the curve = 85%). CHIT1 was the best discriminator of chronic active versus chronic inactive lesions and the only marker correlated with NfL ( r = 0.3, p = 0.0019). Associations with disease activity were, however, independent of NfL. Interpretation: CHIT1 CSF levels measured during the diagnostic LP reflect microglial activation early on in MS and can be considered a valuable prognostic biomarker for future disease activity. ANN NEUROL 2020;87:633–645